2020
DOI: 10.1177/0840470420938818
|View full text |Cite
|
Sign up to set email alerts
|

Virtual care: Enhancing access or harming care?

Abstract: COVID-19 has catalyzed the adoption of virtual medical care in Canada. Virtual care can improve access to healthcare services, particularly for those in remote locations or with health conditions that make seeing a doctor in person difficult or unsafe. However, virtual walk-in clinic models that do not connect patients with their own doctors can lead to fragmented, lower quality care. Although virtual walk-in clinics can be helpful for those who temporarily lack access to a family doctor, they should not be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 7 publications
3
101
1
1
Order By: Relevance
“…20,21 Concerns have been raised about virtual visits, including privacy, continuity of care and equity of implementation. 21,22 An Ontario pilot study of virtual care showed that, when provided with a choice of audio, video or text messaging on an integrated platform, more than 90% of visits occurred using asynchronous, secure text messaging followed by audio, yet there are no billing codes for text messaging. 28 Despite extensive use of virtual care in the COVID-19 pandemic, [23][24][25][26][27] the appropriate role of virtual care remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Concerns have been raised about virtual visits, including privacy, continuity of care and equity of implementation. 21,22 An Ontario pilot study of virtual care showed that, when provided with a choice of audio, video or text messaging on an integrated platform, more than 90% of visits occurred using asynchronous, secure text messaging followed by audio, yet there are no billing codes for text messaging. 28 Despite extensive use of virtual care in the COVID-19 pandemic, [23][24][25][26][27] the appropriate role of virtual care remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…videoconference or telephone) has rapidly expanded to meet patient needs and physical distancing guidelines during the COVID-19 pandemic [ 1–3 ]. Before the COVID-19 pandemic, virtual care was often used to provide medical care to older adults from rural and distant communities in Canada; however, it is now being used routinely in urban settings [ 1 ]. Although virtual care is a way for clinicians to continue caring for patients throughout the COVID-19 pandemic, certain factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…• Concerns about virtual visits include difficulty building rapport and risks to follow-up and continuity of care. 6,7 -Continuity of care results in lower costs, hospitalizations, and mortality in the long term. 8,9 • Diagnostic error is difficult to assess.…”
Section: Contextmentioning
confidence: 99%